Self-repairing double-layer packaging aggregate based on bone bionics and preparation method and application thereof

Through bone bionic technology, self-healing double-layer encapsulated aggregate is used to generate hydroxyapatite in cement-based materials, solving the problem of low self-repair efficiency of cracks of cement-based materials, improving the durability and stability of the materials, and achieving economical and environmentally friendly repair effects.

CN119263680APending Publication Date: 2025-01-07BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531069.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Cement-based materials are prone to cracking under external load, shrinkage, temperature gradient and expansion reactions, resulting in reduced strength and durability. It is difficult for existing self-repair technologies to effectively control and improve repair efficiency.

Method used

Using self-healing double-layer encapsulated aggregate based on bone bionics, hydroxyapas are generated at the cracks by using a combination structure of porous ceramic carrier impregnated with phosphate repair agent, internal adhesive layer and external consolidation layer. stone, realize independent restoration.

Benefits of technology

It improves the durability and durability of cement-based materials, ensures the stability and biocompatibility of repair products, and enhances the economic and environmental friendliness of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263680A_ABST
    Figure CN119263680A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based crack self-repairing, in particular to a self-repairing double-layer packaging aggregate based on bone bionics as well as a preparation method and application of the self-repairing double-layer packaging aggregate. The self-repairing double-layer packaging aggregate comprises a porous ceramsite carrier impregnated with a phosphate repairing agent, an internal bonding layer and an external consolidation layer, the internal bonding layer is formed by a bonding material coating the surface of the porous ceramsite carrier; the binding material comprises a binding agent, a curing agent and a diluent; and the external consolidation layer is formed by curing an inorganic material adhered to the surface of the internal bonding layer. The self-repairing double-layer packaging aggregate provided by the invention has better cohesiveness and compatibility with a cement base material, is internally porous, can be used as a container of a repairing agent, and has better long-term stability; the durability of the cement-based material can be improved, so that the cement-based material has better economical efficiency and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based crack self-repairing, and in particular to a self-repairing double-layer encapsulated aggregate based on bone bionics, and a preparation method and application thereof. Background Art

[0002] Cement-based materials are the most widely used building materials, but they are prone to cracking under tensile stress caused by external loads, shrinkage, temperature gradients, and expansion reactions, resulting in reduced strength and long-term performance. If not repaired in time, macro cracks will be induced, which will further reduce strength and carbonization, affecting its durability and service life. Therefore, it is particularly necessary to be able to sense and autonomously repair cracks in cement-based materials in a timely manner to prevent the development and spread of cracks. The self-repair process of cracks in cement-based materials can be divided into two categories: autogenous repair and autonomous repair. Autogenous repair originates from the further hydration or carbonation of unhydrated cement particles and is an inherent ability of cement materials. However, this naturally occurring process is difficult to control and has limited repair efficiency. Autonomous repair is an artificially designed process that is achieved by pre-implanting crack repair materials and has great application potential.

[0003] Self-healing cement-based materials imitate the function of biological tissues to automatically secrete certain substances to the injured part to make it heal. Special components are compounded in the traditional components of cement materials to form an intelligent self-healing system inside the cement matrix. The design concept of the present invention comes from the principle of bone bionics. The inorganic substances in human bones are mainly calcium and phosphorus. The presence of these two substances makes the bones have a certain hardness. Inspired by the self-repair of bones, the mechanism of the repair system in organisms is applied to cement-based materials. The principle is to generate hydroxyapatite by chemical precipitation in a cement environment, use active phosphates to provide a phosphorus source, and the cement matrix provides a calcium source. The cement pore solution provides an alkaline environment, and hydroxyapatite is generated in situ at the cracks, thereby achieving the purpose of self-repairing cracks.

[0004] When cracks occur, in order to respond intelligently and release repair components, the self-repairing components need to be loaded with carriers. Encapsulation is a common packaging method. The mechanical strength of the capsule and its interface bonding strength determine whether the capsule can respond to rupture in time when cracks occur. Therefore, it is necessary to select a packaging material that has good compatibility with cement materials. In view of this, the present invention is proposed. Summary of the invention

[0005] Inspired by bone repair, the present invention uses hydroxyapatite as a cement-based material self-repair product. In order to maintain long-term repair function and increase the probability of intelligent response to cracks, a self-repairing double-layer encapsulated aggregate based on bone bionics and its preparation method and application are provided.

[0006] Specifically, the technical solution of the present invention is as follows: In the first aspect, the present invention provides a self-healing double-layer encapsulated aggregate, which includes a porous expanded clay carrier impregnated with a phosphate repair agent, an internal bonding layer and an external consolidation layer; the internal bonding layer is formed by a bonding material coated on the surface of the porous expanded clay carrier; the bonding material includes a bonding agent, a curing agent and a diluent; the external consolidation layer is formed by curing an inorganic material adhered to the surface of the internal bonding layer.

[0007] The self-repairing double-layer encapsulated aggregate provided by the present invention has good adhesion and compatibility with the cement substrate, and the self-repairing double-layer encapsulated aggregate has many internal pores, and can achieve an effect similar to that of capsule-coated core material by impregnating the repair agent solution. In the structure of the self-repairing double-layer encapsulated aggregate of the present invention, the internal bonding layer can not only encapsulate the repair agent but also play the role of an intermediate bridge, and can tightly bond the external consolidation layer to the aggregate, thereby avoiding the porous ceramsite carrier and the external consolidation layer from falling off. The external consolidation layer is mainly used to enhance the compatibility between the self-repairing double-layer porous aggregate and the cement matrix, forming a good interface transition zone to ensure that the ceramsite can break as the cement matrix cracks. In order to achieve the above purpose, the structure of the prepared double encapsulation layer is that the internal bonding layer and the external consolidation layer are interlocked together, and an interlocking surface is formed on the outer layer of the porous ceramsite carrier, so as to avoid the problem of premature release of the repair agent of the double-layer encapsulated aggregate during the mixing of the concrete slurry, so as to ensure the self-repairing efficiency and long-term repair function of the double-layer encapsulated aggregate.

[0008] Preferably, the adhesive is a curable polymer resin adhesive.

[0009] More preferably, the adhesive is at least one of epoxy resin, polyurethane, urea-formaldehyde resin, and phenol-formaldehyde resin; more preferably, epoxy resin.

[0010] The curing agent for the epoxy resin is preferably an amine curing agent and / or an acid anhydride curing agent; more preferably tetraethylenepentamine.

[0011] Preferably, the mass ratio of the adhesive, the curing agent and the diluent is 1:(0.07-0.14):(0.03-0.05); more preferably 1:0.12:0.04.

[0012] Preferably, the porous ceramsite carrier is selected from at least one of clay ceramsite, fly ash ceramsite and shale ceramsite, and clay ceramsite is more preferred. Clay ceramsite has a better water absorption effect. When cracks appear in the cement matrix, clay ceramsite is preferably used as a loading material for phosphate repair agents such as sodium dihydrogen phosphate solution to provide more phosphate groups for the cracks.

[0013] Preferably, the phosphate repair agent is selected from at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate.

[0014] Preferably, the inorganic material forming the outer consolidation layer is selected from at least one of silicate cement powder, silica fume, fly ash, kaolin, and quartz sand; more preferably, it is silicate cement powder.

[0015] Preferably, the mass proportion of the phosphate repair agent in the self-repairing double-layer encapsulated aggregate is 20%~30%; and / or the mass proportion of the porous expanded clay carrier in the self-repairing double-layer encapsulated aggregate is 35%~50%; and / or the mass proportion of the internal bonding layer in the self-repairing double-layer encapsulated aggregate is 3.5%~5.0%; and / or the mass proportion of the external consolidation layer in the self-repairing double-layer encapsulated aggregate is 25%~35%.

[0016] More preferably, the mass proportion of the phosphate repair agent in the self-repairing double-layer encapsulated aggregate is 24%~26%; and / or the mass proportion of the porous expanded clay carrier in the self-repairing double-layer encapsulated aggregate is 41%~43%; and / or the mass proportion of the internal bonding layer in the self-repairing double-layer encapsulated aggregate is 4.0%~4.5%; and / or the mass proportion of the external consolidation layer in the self-repairing double-layer encapsulated aggregate is 28%~30%.

[0017] In a second aspect, the present invention provides a method for preparing the self-healing double-layer encapsulated aggregate, comprising: selecting a porous ceramsite carrier to load active phosphate; preparing materials required for an internal bonding layer, coating the porous ceramsite carrier that has been loaded with active phosphate to form an internal bonding layer; and encapsulating the porous ceramsite carrier that has been coated with the internal bonding layer with an external consolidation layer.

[0018] Preferably, the loading method is: immersion at -0.08 to -0.12 MPa for 0.5 to 1.5 h.

[0019] More preferably, the loading method is: immersion at -0.1 MPa for 45 min.

[0020] In a third aspect, the present invention provides the use of the self-repairing double-layer encapsulated aggregate or the self-repairing double-layer encapsulated aggregate prepared by the preparation method in cement-based crack self-repair.

[0021] The present invention introduces biological bone bionics technology and uses the principle of preparing hydroxyapatite by chemical precipitation in a cement environment. Active phosphate provides a phosphorus source, the cement matrix provides a calcium source, and the cement pore solution provides an alkaline environment. Hydroxyapatite minerals are generated in situ at the cracks to repair the cracks.

[0022] Beneficial effects: The present invention provides a self-repairing double-layer packaged aggregate and a preparation method and application thereof, wherein the self-repairing double-layer packaged aggregate comprises a porous ceramsite carrier impregnated with a phosphate repair agent, an internal bonding layer and an external consolidation layer; the internal bonding layer is formed by a bonding material coated on the surface of the porous ceramsite carrier; the bonding material comprises an adhesive, a curing agent and a diluent; the external consolidation layer is formed by curing an inorganic material adhered to the surface of the internal bonding layer. The self-repairing double-layer packaged aggregate provided by the present invention has good adhesion and compatibility with a cement substrate, the aggregate has a certain strength and is porous inside, and can be used as a container for a repair agent, so that it can remain intact during concrete mixing and has better long-term stability; the good interface bonding force between the aggregate shell and the cement matrix can ensure that the ceramsite responds in time when cracks occur, and releases the internal phosphate repair agent to self-repair the cracks; the repair products are closely stacked in a spherical shape around the cracks, forming a relatively dense repair product layer, which can better restore the material performance and improve the durability of cement-based materials, so that the present invention has better economy and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be described below.

[0024] Figure 1 It is a schematic diagram of the self-repairing principle of the self-repairing porous aggregate based on bone bionics in cement-based materials of the present invention.

[0025] Figure 2 These are the mass loss results of the aggregate only treated by impregnation, the aggregate only treated by the internal bonding layer, and the double-layer encapsulated aggregate described in Example 2 of the present invention.

[0026] Figure 3 This is a histogram of crack width distribution on the surface of the sample described in Example 3 of the present invention.

[0027] Figure 4 These are photos of the cement-based self-repairing system described in Example 3 of the present invention, before and after self-repair of a surface crack with a width of 300 μm.

[0028] Figure 5 This is a SEM image of the crack repair product of the cement-based self-repairing system described in Example 3 of the present invention.

[0029] Figure 6 This is the compressive strength recovery result of the cement-based self-repairing system described in Example 4 of the present invention after 28 days of repair after pre-compression. DETAILED DESCRIPTION

[0030] The present invention provides a self-repairing double-layer encapsulated aggregate based on bone bionics, and a preparation method and application thereof. The self-repairing double-layer encapsulated aggregate has good adhesion and compatibility with cement substrates. The aggregate is porous inside and can be used as a container for a repair agent. The structure includes a porous ceramsite carrier, a repair agent, an internal bonding layer, and an external consolidation layer. The double-layer encapsulated aggregate of the present invention can be applied to cement-based materials to construct a new type of cement-based self-repairing system based on bone bionics. Inspired by bone repair, the present invention applies the mechanism of a repair system similar to that in an organism to a self-repairing cement material, using active phosphates to provide a phosphorus source, cement matrix to provide a calcium source, and cement pore solution to provide an alkaline environment to generate hydroxyapatite at the cracks to repair the cracks. Hydroxyapatite has better biocompatibility and stability, and can improve the durability of cement-based materials, making the present invention economical and environmentally friendly.

[0031] In a more specific embodiment, the technical solutions provided by the present invention include: A self-repairing double-layer encapsulated aggregate based on bone bionics, comprising a porous ceramsite carrier, an internal bonding layer, and an external consolidation layer; wherein the porous ceramsite carrier is vacuum impregnated so that a phosphate repair agent fills the pores of the porous ceramsite carrier, providing active phosphate, aiming to chemically precipitate hydroxyapatite at the cracks.

[0032] A method for preparing a self-repairing double-layer encapsulated aggregate based on bone bionics comprises the following steps: (1) preparing a phosphate repair agent solution; wherein the phosphate repair agent solution is one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, and sodium phosphate.

[0033] (2) Add a porous ceramsite carrier to the phosphate repair agent solution in step (1) for loading treatment. The porous ceramsite carrier is selected from one or more combinations of clay ceramsite, fly ash ceramsite, and shale ceramsite. The loading treatment is to immerse for 0.5-1.5 hours under a vacuum condition of -0.1MPa so that the solution can be fully filled into the pores of the porous ceramsite carrier. Then take out the porous ceramsite carrier filled with phosphate repair agent and remove excess water on the surface.

[0034] (3) Providing materials required for the internal bonding layer, and uniformly coating the materials required for the internal bonding layer on the surface of the porous ceramsite carrier filled with phosphate repair agent in step (2) to form an internal bonding layer. The method for preparing the materials required for the internal bonding layer includes the following steps: mixing and stirring the adhesive and the diluent to obtain an adhesive dilution; adding a curing agent to the adhesive dilution and stirring to obtain the materials required for the internal bonding layer. The mass ratio of the adhesive, the curing agent, and the diluent is 1:0.12:0.04.

[0035] (4) The porous ceramsite coated with the internal bonding layer in step (3) is rolled in cement to form an external consolidation layer on the surface of the internal bonding layer and to evenly disperse the porous ceramsite coated with the bonding layer, and then cured at room temperature for 24 hours to obtain a self-healing double-layer encapsulated aggregate.

[0036] The repair principle of the self-repairing double-layer encapsulated aggregate provided by the present invention is mainly based on the following aspects: When cracks occur in the cement matrix, the cracks propagate through the matrix and cause the porous aggregate to be damaged. When external water penetrates into the cracks, the cement matrix releases Ca under the immersion of water. 2+ and OH - The phosphate groups impregnated in the aggregate penetrate along the cracks under the action of osmotic pressure and interact with the Ca in the matrix. 2+ Meet, Ca 2+ With PO4 3- The reaction generates small spherical amorphous calcium phosphate that adheres to both sides of the crack; over time, the crack repair product is transformed from small spherical amorphous calcium phosphate into hydroxyapatite with good stability, further improving the repair effect.

[0037] The present invention introduces biological bone bionic technology, the principle of which is to prepare hydroxyapatite by chemical precipitation in a cement environment, using active phosphate to provide a phosphorus source, cement matrix to provide a calcium source, and cement pore solution to provide an alkaline environment, and to generate hydroxyapatite minerals in situ at the cracks to repair the cracks, thereby improving the strength and durability of the cement-based material after repair.

[0038] The present invention selects porous ceramsite as the repair agent carrier, and fills the porous ceramsite carrier with the repair agent through vacuum impregnation. In order to maintain the long-term effectiveness of the repair agent, the aggregate encapsulated by the double layer (internal bonding layer and external curing layer) not only maintains a good survival rate during the mixing of the concrete slurry to avoid the premature release of the repair agent, but also the external consolidation layer can enhance the compatibility between the double-layer encapsulated aggregate and the cement matrix, forming a good interface transition zone, which can break as the cement matrix cracks, ensuring good triggering.

[0039] The invention has reasonable economy and environmental friendliness. The preparation method of the double-layer encapsulated aggregate is simple, the raw material price is low, and the reaction during the preparation process is pollution-free. In addition, phosphate is used as a repairing agent to directly generate hydroxyapatite at the crack, which is the main inorganic component of human and animal bones. Hydroxyapatite has better biocompatibility and stability, and the entire reaction process does not produce other pollution, which has better environmental friendliness.

[0040] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The endpoints and any values ​​of the ranges disclosed in this specification are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0042] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementations", or "some specific implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0043] In the examples provided in this specification, if no specific techniques or conditions are specified, the techniques or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.

[0044] Embodiment 1: This embodiment provides three double-layer encapsulated aggregates (S-2, S-3, and S-4) for cement-based crack self-repair.

[0045] The three double-layer encapsulated aggregates provided in this embodiment are prepared by the following steps: (1) Impregnation of repair liquid: sieve out some 4-8mm porous ceramsite carriers, put the porous ceramsite carriers into a 100℃ constant temperature blast drying oven and dry them to constant weight, and weigh 200g. Prepare sodium dihydrogen phosphate solutions with mass fractions of 20%, 30%, and 40%, respectively, then pour the aggregate and sodium dihydrogen phosphate solutions with mass fractions of 20%, 30%, and 40% into a vacuum dish, use a ceramic sheet to completely immerse the porous ceramsite in the repair agent solution, turn on the vacuum pump and immerse for 45 minutes at -0.1Mpa. Use a towel to wipe off excess moisture on the surface of the porous ceramsite to improve the bonding ability between the surface of the porous ceramsite and the internal consolidation layer.

[0046] (2) Preparation of materials required for the internal bonding layer: In this embodiment, epoxy resin is used for the inner layer packaging of porous ceramsite. After curing, epoxy resin can effectively prevent the repair agent from seeping into the cement matrix due to humidity gradient and osmotic pressure, causing the loss of the repair agent, and the bonding layer can bond the loaded aggregate to the cement packaging layer to avoid separation between layers. However, the viscosity of epoxy resin is too high, which may affect the packaging effect of the aggregate. Therefore, in this embodiment, the consistency of epoxy resin is adjusted by adding an appropriate amount of diluent, and the normal polymerization reaction of epoxy resin and curing agent is also ensured. In this embodiment, the ratio of materials required for the bonding layer is epoxy resin: curing agent: diluent = 1: 0.12: 0.04. The specific production method is: pour 100g of epoxy resin and 4g of epoxy diluent (1,4-butanediol diglycidyl ether) into a beaker, and dilute the epoxy resin under 60°C water bath heating conditions. Then, add 12g of curing agent (tetraethylenepentamine, TEPA) and stir until the color is consistent and there is no stratification, thus obtaining the material required for the desired internal bonding layer.

[0047] (3) Internal bonding layer coating: The porous expanded clay and the materials required for the internal bonding layer are uniformly mixed in a ratio of 10:1. The mixture is allowed to stand for 2 minutes to allow the materials required for the internal bonding layer to infiltrate the surface of the porous expanded clay from top to bottom. The porous expanded clay is stirred at a constant speed for 2 minutes using a glass rod to completely coat the surface of the porous expanded clay.

[0048] (4) External consolidation layer encapsulation: The porous ceramsite coated with the internal consolidation layer is rolled in cement powder so that the surface is evenly adhered to the cement powder and dispersed. Then, the internal bonding layer is allowed to completely solidify for 24 hours, and the excess cement powder is sieved out with a 2.36 mm standard sieve to obtain the self-repairing double-layer encapsulated aggregate based on bone bionics. The samples are numbered corresponding to the phosphate solutions with mass fractions of 20%, 30%, and 40% impregnated, and the samples are numbered S-2, S-3, and S-4, respectively.

[0049] In this embodiment, the prepared double-layer encapsulated aggregate is taken as the total mass, and the proportions of each structure: porous expanded clay carrier, repair agent, internal bonding layer, and external consolidation layer are calculated as shown in Table 1 below.

[0050]

[0051] Embodiment 2: This example experiments on the encapsulation effect of different aggregates containing repairing agents.

[0052] The experimental contents of this embodiment are as follows: Take a certain amount of aggregate that has been treated with only impregnation (prepared according to step (1) of Example 1), aggregate that has only been treated with the internal bonding layer (prepared according to steps (1) and (2) of Example 1), and double-layer encapsulated aggregate (the self-repairing double-layer encapsulated aggregate finally obtained in Example 1), and divide the aggregate in each treatment state into 3 portions, each portion is 100g±0.1g, and the initial mass is recorded as m0. The aggregates in these three treatment states are placed in an oven at 60°C for drying, and taken out every 30 minutes for the first 2 hours, and placed at room temperature (T=23°C) for 5 minutes. After the temperature of the aggregate surface cools down, the mass is recorded, and the mass loss rate within 0.5h, 1h, 1.5h, 2h, 4h, and 12h is tested. The mass loss rate is calculated using the following formula (1):

[0053] Where: D——the percentage of sample mass loss at time t, %; m0——initial sample mass, g; m t ——The mass of the sample at time t, g.

[0054] Figure 2 The mass loss rates of the aggregates treated with only impregnation, only internal bonding layer and double-layer packaging are given. It can be found from the figure that the mass loss of the double-layer packaging aggregate is only 6.81% after being placed at 60℃ for 12 hours, the mass loss of the aggregates treated with only impregnation is 25.92%, and the mass loss of the aggregates treated with only internal bonding layer is 10.59%. Under the general internal temperature conditions of concrete, this double-layer packaging method guarantees a good packaging effect to a certain extent.

[0055] Embodiment 3: This embodiment provides the application of the double-layer encapsulated aggregate in cement-based crack self-repair.

[0056] The application method described in this embodiment includes: Weigh 450g of ordinary Portland cement and 225g of water, and stir mechanically for 60s under a low-speed stirring paddle; continue to uniformly add the double-layer encapsulated aggregate described in Example 1 within the second 60s, replace 20% of the mass of standard sand with aggregate, then add 1080g of standard sand, and continue stirring for 120s. Pour the mixture into a mold (40mm×40mm×160mm). In order to vibrate evenly and prevent segregation, all samples are cast in layers. The mixture is poured into the corresponding mold twice in succession. First, inject the slurry of 1 / 2 height of the mold, and vibrate the slurry for 10s using a vibrating table. For samples that need to arrange wire mesh, place the wire mesh during layered casting, and then inject the remaining slurry. After vibrating for 20s, use a spatula to smooth the surface of the sample. After casting the specimen, cure it for 24h under standard curing conditions (relative humidity above 95%, temperature 20℃±2℃). After the curing is completed, the formwork is removed and standard curing is carried out until the 7-day age.

[0057] In order to obtain a specimen with an ideal crack width, a notch with a depth of 3mm was made in the middle of the bottom of the specimen before the three-point bending test. After the notch was made, the specimen was loaded using a compression and flexural integration testing machine at a loading speed of 0.1mm / min for a three-point bending test. The width of the crack was detected using a comprehensive crack detector. When the crack at the notch reached the preset width, the loading was stopped and the width at this time was observed and recorded. Using the comprehensive crack observation instrument, 3 points were selected at the same interval to measure the distribution of the crack width. A total of 108 points were measured for all specimens. Figure 3 The crack width distribution histogram is given, and the crack width is concentrated in the range of 100-300 μm. After the specimen was placed in static water curing conditions for 28 days, it was observed and measured again at the same position.

[0058] After 28 days of hydrostatic curing, crystallization appeared on the surface of all samples. Figure 4 The photos of the sample with a crack width of 300μm before and after self-repair are given. It can be found that the crack has become smaller in width, and white crystalline repair products have been produced. The repair products basically fill the crack and grow from both sides of the crack to the center.

[0059] Figure 5 The SEM image of the repair product at the crack after 28 days of hydrostatic curing of the sample is given. The repair products are mostly clustered spherical crystals with a diameter of about 1-5μm. The spherical structure is a typical structure of hydroxyapatite. The repair products are spherically stacked around the cracks to form a relatively dense repair product layer, thereby improving the durability of cement-based materials.

[0060] Embodiment 4: This example verifies the cement-based crack self-repairing effect of the double-layer encapsulated aggregate (compressive strength recovery rate 28 days after repair after pre-compression).

[0061] The verification method described in this embodiment includes: Weigh 450g of ordinary Portland cement and 225g of water, and stir mechanically for 60s under a low-speed stirring paddle; continue to evenly add the aggregate described in Example 1 within the second 60s, replacing 20% ​​of the mass of the standard sand with aggregate, then add 1080g of standard sand and continue stirring for 120s. Pour the freshly mixed cement into a mold (40mm×40mm×160mm), and after the specimen is cast, cure it under standard curing conditions (relative humidity above 95%, temperature 20℃±2℃) for 24h. After the curing is completed, remove the mold and perform standard curing until the age of 28d. First, use a compression and flexural integrated testing machine to test the maximum compressive strength of the mortar. Six parallel samples are grouped together, and the average value after the test is taken as F max . Set the maximum preload to 40%F max , load to the set preload force at a speed of 200N / s, maintain pressure for 120s and then unload, repair under static water conditions for 28d, and then test its compressive strength, and calculate the repair efficiency according to formula (2).

[0062]

[0063] Where: λ p ——Recovery rate of compressive strength due to load damage, %; f c ——40%F max Compressive strength of preload damaged specimen, MPa; f 0——0%F max Preload versus compressive strength of specimen, MPa.

[0064] When the preload is 40%F max When the cement mortar specimens added with the aggregate were repaired, their compressive strength recovery rate exceeded 100%. Figure 6 In a hydrostatic curing environment, water can promote the formation of hydroxyapatite at the cracks, achieve self-repair of the cracks, and improve the strength of the specimens.

[0065] In summary, the present invention provides a self-repairing double-layer encapsulated aggregate based on bone bionics, and applies it to cement-based materials to construct a new cement-based self-repairing system. The present invention applies the mechanism of the repair system in organisms to cement-based materials, introduces the basic principle of preparing hydroxyapatite by chemical precipitation into the cement environment, uses embedded active phosphate to supply phosphorus, calcium ions dissolved in the cement matrix to supply calcium, and cement pore solution to provide an alkaline environment, and generates hydroxyapatite at the cracks through chemical precipitation to achieve self-repair of the cracks, thereby improving the durability of cement-based materials.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. Self-repairing double-layer encapsulated aggregate, characterized in that: It includes a porous ceramsite carrier impregnated with a phosphate repair agent, an internal bonding layer and an external consolidation layer; the internal bonding layer is formed by a bonding material coated on the surface of the porous ceramsite carrier; the bonding material includes an adhesive, a curing agent and a diluent; the external consolidation layer is formed by curing an inorganic material adhered to the surface of the internal bonding layer.

2. The self-repairing double-layer encapsulated aggregate according to claim 1, characterized in that: The adhesive is a curable polymer resin adhesive; preferably at least one of epoxy resin, polyurethane, urea-formaldehyde resin, and phenolic resin; more preferably epoxy resin; The curing agent for the epoxy resin is preferably an amine curing agent and / or an acid anhydride curing agent; more preferably tetraethylenepentamine.

3. The self-repairing double-layer encapsulated aggregate according to claim 1 or 2, characterized in that: The mass ratio of the adhesive, the curing agent and the diluent is 1:(0.07-0.14):(0.03-0.05); preferably 1:0.12:0.

04.

4. The self-repairing double-layer encapsulated aggregate according to any one of claims 1 to 3, characterized in that: The porous ceramsite carrier is selected from at least one of clay ceramsite, fly ash ceramsite and shale ceramsite, and is preferably clay ceramsite.

5. The self-repairing double-layer encapsulated aggregate according to any one of claims 1 to 4, characterized in that: The phosphate repair agent is selected from at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium phosphate.

6. The self-repairing double-layer encapsulated aggregate according to any one of claims 1 to 5, characterized in that: The inorganic material forming the outer consolidation layer is selected from at least one of silicate cement powder, silica fume, fly ash, kaolin, and quartz sand; preferably silicate cement powder.

7. The self-repairing double-layer encapsulated aggregate according to any one of claims 1 to 6, characterized in that: The mass proportion of the phosphate repair agent in the self-repairing double-layer encapsulated aggregate is 20%~30%; and / or the mass proportion of the porous expanded clay carrier in the self-repairing double-layer encapsulated aggregate is 35%~50%; and / or the mass proportion of the internal bonding layer in the self-repairing double-layer encapsulated aggregate is 3.5%~5.0%; and / or the mass proportion of the external consolidation layer in the self-repairing double-layer encapsulated aggregate is 25%~35%.

8. The method for preparing the self-repairing double-layer encapsulated aggregate according to any one of claims 1 to 7, characterized in that: include: A porous ceramsite carrier is selected to load the active phosphate; the materials required for the internal bonding layer are prepared, and the porous ceramsite carrier that has been loaded with the active phosphate is coated to form the internal bonding layer; and the porous ceramsite carrier that has been coated with the internal bonding layer is encapsulated with an external consolidation layer.

9. The preparation method according to claim 8, characterized in that: The loading method is: immersing at -0.08~-0.12MPa for 0.5~1.5h; preferably: immersing at -0.1MPa for 45min.

10. The self-repairing double-layer encapsulated aggregate according to any one of claims 1 to 7 or the self-repairing double-layer encapsulated aggregate prepared by the preparation method according to claim 8 or 9 is used for autonomous repair of cracks in cement-based materials.